Fukushimura BrainBank project, Japan: Human neuropathology/clinico‐pathologic correlations. (7th December 2020) - Kaneda, Daita; Akatsu, Hiroyasu; Ogawa, Norihiro; Kanesaka, Takeshi; Hishida, Chie; Yamamoto, Sakon; Yamamoto, Takayuki; Yoshio, Hashizume
Abstract: Background: The Fukushimura (welfare village), located in Toyohashi city, Japan, is a unique complex of various nursing home facilities including dementia homes, Day‐care houses, homes for disabled and mentally retarded, and the Fukushimura Hospital. This village is totally managed by private sector, the Sawarabi Medical Cooperative. About 800 elderly people reside in this area. The hospital plays a pivotal role within the village and acts as the central facility for each nursing homes. Fukushimura BrainBank (FBB) was established in 1990. The neuropathological investigation of FBB was initially conducted by Kenji Kosaka, who initially reported cortical Lewy bodies. Our research institute was approved in 2004 by the Ministry of Education, Culture, Sports, Science and Technology, as one of the non‐governmental institutes which is permitted to apply for governmental grants. Method: For collecting CNS specimens, the brains are separated into two hemispheres, one for neuropathological analyses with using several antibodies for beta‐amyloid, phosphorylated tau, alpha‐synuclein, and TDP‐43. Modified gallyas‐silver staining is applied for evaluating argyrophilic grain disease. The other hemispheres are stored for frozen sections. All the medical records and radiological images from the nursing home to hospital are stored in the research institute, which make it possible for the researchers to access the psychological symptoms observed by carers in the long duration of the disease. Result: The number of autopsy became over 30 cases per year. Most of the patients had dementia or chronic devastating cerebrovascular diseases. Of note, geriatric residents with mentally retardation or cerebral palsy from childhood were included. At the end of 2019, more than 720 of frozen brains with detailed medical record are stored in FBB and readily available for research. The neuropathology database share the same coding system for Japanese Brain Bank Network for Neuroscience Research (JBBNNR). We already have over 20 collaborators and supply our samples for more than 30 research institutes in Japan. Conclusion: The challenge of FBB will play a unique and important role to clarify cliniconeuropathological correlation of the nursing home residential with various geriatric conditions, especially from the point of view of nursing staffs.